Rani Creative House Marketing Communication Strategy In Promoting Knitting Products - Novy Arisca; Yuniar Pangesti; Dita Ananda Bangun; Bunga Dwi Anjani; Suhairi Suhairi (Lembaga Riset dan Inovasi Al-Matani, 2023)
This study aims to find out more about marketing communication strategies in promoting Rani Creative House knitting products as well as the supporting and inhibiting factors in promoting Rani Creative House knitting products. This research use desciptive qualitative approach. The data obtained from the results of interviews and documentation. The theory used is integrated marketing communication (integrated marketing communication). The results show that in promoting their products, Rumah Kreatif Rani carries out a communication process by implementing a communication strategy that includes communication components, namely sources, messages, media, recipients, effects and feedback. In addition, Rani Creative House also uses the IMC (Integrated Marketing Communication) theory which shows that advertising activities (advertising), direct marketing and sales promotion are effective and efficient marketing communication activities for Rani Creative House in promoting products. Some of the activities carried out by Rani Creative House in promoting their products are taking product photos, using social media WhatsApp, Facebook and Instagram as promotional media and giving discounts to consumers. Factors supporting Rani Creative House in promoting its knitting products are affordable promotional costs, easy internet access, and a broad target market. While the inhibiting factors are the limited staff to take product photos, limited staff to promote and store locations that are difficult to reach are taking product photos, using social media WhatsApp, Facebook and Instagram as promotional media and giving discounts to consumers. Factors supporting Rani Creative House in promoting its knitting products are affordable promotional costs, easy internet access, and a broad target market. While the inhibiting factors are limited personnel to take product photos, limited personnel to promote and store locations that are difficult to reach are taking product photos, using social media WhatsApp, Facebook and Instagram as promotional media and giving discounts to consumers. Factors supporting Rani Creative House in promoting its knitting products are affordable promotional costs, easy internet access, and a broad target market. While the inhibiting factors are limited personnel to take product photos, limited personnel to promote and store locations that are difficult to reach.